Pengaruh Penerapan Sistem Informasi Akuntansi Manajemen, Sistem Pengukuran Kinerja dan Sistem Penghargaan terhadap Kinerja Manajerial pada PT. BBI Indonesia - Syafira P, Putri Adeliza (STAI Denpasar Bali, 2024)
Management accounting information systems as systems that play a role in helping predict the possible consequences of several alternative actions taken in various activities such as planning, controlling and decision making are useful in helping managers fulfill their contribution in achieving managerial performance. The performance measurement system shows the relationship between the plans that have been set by the company and the results achieved which will provide information about the achievement of implementing a plan. Reward system as a motivator for employees in realizing company goals. This research aims to find out whether the implementation of a management accounting information system, performance measurement system, and reward system simultaneously influences managerial performance. The approach used is a quantitative approach. The location of this research was carried out at PT. BBI (Boma Bisma Indra) Indonesia whose address is Jalan Pulau Pinang VI-VII, KIM II, Medan, the population in this study were all employees totaling 53 people. The sampling technique used was saturated sampling where the entire population of 53 people was sampled and The data analysis technique used is multiple linear regression analysis. The results of this research are that in this research, the Management Accounting Information System partially has a positive and significant effect on the Managerial Performance of PT BBI (Boma Bisma Indra). In this research, the performance measurement system partially has a positive and significant effect on the managerial performance of PT. BBI (Boma Bisma Indra). In this research, the reward system partially has a positive and significant effect on the managerial performance of PT BBI (Boma Bisma Indra). In this study the independent variables consisting of the management accounting information system, performance measurement system, reward system together influence the performance of PT BBI (Boma Bisma Indra) employees.